2015
DOI: 10.1002/stem.1925
|View full text |Cite
|
Sign up to set email alerts
|

p53 Loss Increases the Osteogenic Differentiation of Bone Marrow Stromal Cells

Abstract: The tumor suppressor, p53, plays a critical role in suppressing osteosarcoma. Bone marrow stromal cells (BMSCs, also known as bone marrow-derived mesenchymal stem cells) have been suggested to give rise to osteosarcomas. However, the role of p53 in BMSCs has not been extensively explored. Here, we report that p53 regulates the lineage choice of mouse BMSCs (mBMSCs). Compared to mBMSCs with wild type p53, mBMSCs deficient in p53 have enhanced osteogenic differentiation, but with similar adipogenic and chondroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 51 publications
4
73
0
Order By: Relevance
“…Pathological analyses revealed that 100% of generated tumors were osteoblastic OS containing woven bones and osteoid (Figure 1). This finding is consistent with our previous in vitro observation showing that p53_KO BMSCs are predisposed to osteoblastic differentiation (He et al., 2015). Thus, the default subtype of OS formed from p53_KO BMSCs is osteoblastic OS.
Figure 1p53_KO BMSCs Generate Osteoblastic OS(A) H&E staining of two representative tumors formed from p53_KO BMSCs transplanted into NSG mice.
…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Pathological analyses revealed that 100% of generated tumors were osteoblastic OS containing woven bones and osteoid (Figure 1). This finding is consistent with our previous in vitro observation showing that p53_KO BMSCs are predisposed to osteoblastic differentiation (He et al., 2015). Thus, the default subtype of OS formed from p53_KO BMSCs is osteoblastic OS.
Figure 1p53_KO BMSCs Generate Osteoblastic OS(A) H&E staining of two representative tumors formed from p53_KO BMSCs transplanted into NSG mice.
…”
Section: Resultssupporting
confidence: 94%
“…The dual roles of cFOS in OS are reminiscent of the dual roles of p53 in BMSCs, in which p53 not only prevents tumorigenesis but also affects the lineage choice of these cells (He et al., 2015). What, then, is the relationship between the roles of cFOS in development and cancer?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not simply the loss of WT p53 that drives cells to cancer. The majority of the p53 mutations found in tumors are missense mutations, resulting in production of full-length protein with only one amino acid change [44, 63]. Many of these mutant p53 exhibit a dominant-negative effect over WT p53, mostly by forming mixed tetramers with diminished DNA binding and transactivation activity [64].…”
Section: Mutant P53 Gain-of-function: More Than Just a Lossmentioning
confidence: 99%